Prevalence of coronary heart disease risk factors among adolescents of Kandy Municipal Council area and evaluation of effect of an intervention to reduce sedentary lifestyle - Bandara, K.M.G.K (My University, 2008)
Four thousand students were selected for component 1 of phase 1, using stratified cluster sampling method. A sub sample of 440 students was randomly selected for component 11 of phase 1 of the study. Four schools were randomly selected for phase 11 of the study. A self administered questionnaire was used to collected from all students in component 11 of phase 1 of the study. Four schools were randomly selected for phase 11 of the study. A self administered questionnaire was used to collect information on behavioral risk factors and measurement of weight, height and blood pressure was carried out to assess overweight and high blood pressure. Information on socioeconomic status of parents of the students was also collected using a self administered questionnaire. In addition, a biochemical assessment of serum lipid and plasma glucose level was carried out in a sub sample of students in component 11. In phase 11, a school based intervention trial was carried out to reduce sedentary behavior and to improve knowledge and attitudes towards coronary heart diseases risk factors among the sub sample of students included in component 1 of phase1, The intervention program was evaluated using a self administered questionnaire. Knowledge on most of the CHD risk factors was satisfactory among the adolescents. The intervention program was successful and it had an effect in reducing physical inactivity and further improvement of knowledge and attitudes towards CHDS risk factors among the adolescents. But the sustainability of improved physical activities, knowledge and attitudes decreased with time. This study demonstrates that the prevalence of some of the behavioral and biological risk factors for CHD was alarmingly high among the adolescents in the urban sector, Health service providers should pay special attention on this emerging issue